2003
DOI: 10.1080/14763140308522823
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a biomechanics concept inventory

Abstract: To help instructors in evaluating innovations in biomechanics instruction, a standardised test of the key concepts taught in the introductory biomechanics course was developed. The Biomechanics Concept Inventory (BCI) consists of 24 questions that test four prerequisite competencies and eight biomechanics competencies. Three hundred and sixty seven students from ten universities throughout the United States took the test at the beginning and the end of the introductory biomechanics course. Analysis of a sub-sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 14 publications
4
12
0
1
Order By: Relevance
“…Decades of research on physics instruction in higher education have shown common conceptual misunderstandings of mechanics by most college D. Kundson 110 students (Halloun and Hestenes, 1985;Hestenes Wells, and Swackhammer, 1992). Recent studies using standardized tests of biomechanical concepts have shown that, as for physics students, kinesiology majors have difficulty in replacing their naïve views of mechanics (McCloskey, 1983) with an understanding of Newtonian mechanics (Knudson, 2004;Knudson et al, 2003).…”
Section: Biomechanical Application Chaosmentioning
confidence: 99%
“…Decades of research on physics instruction in higher education have shown common conceptual misunderstandings of mechanics by most college D. Kundson 110 students (Halloun and Hestenes, 1985;Hestenes Wells, and Swackhammer, 1992). Recent studies using standardized tests of biomechanical concepts have shown that, as for physics students, kinesiology majors have difficulty in replacing their naïve views of mechanics (McCloskey, 1983) with an understanding of Newtonian mechanics (Knudson, 2004;Knudson et al, 2003).…”
Section: Biomechanical Application Chaosmentioning
confidence: 99%
“…Los estudiantes se han documentado con la bibliografía aportada, respondiendo a una serie de preguntas que configuran la autoevaluación del estudiante y que le han mostrado su nivel de adquisición de los conocimientos, basándose en biomecánica cualitativa (Hamill, 2007;Knudson, 2007). La evaluación ha estado basada en el Biomechanics Concept Inventory (BCI), (Knudson et al, 2003), mediante 24 cuestiones de elección múltiple sobre contenidos generales de biomecánica deportiva.…”
Section: Primera Etapa: Teoría Documentación Y Análisis (Primera Semunclassified
“…The New Zealand curriculum and the National Certificate of Educational Achievement (NCEA) favor a constructivist approach to Physical Education pedagogy, but this is not reflected as strongly in the actual practice of teaching [4]. Specifically, biomechanics is a discipline that is well positioned for hands-on, student-centered learning; but it is often the teacher's discomfort with biomechanical content that prohibits more engaged interaction [4,5] and can ultimately hinder student learning.…”
Section: Introductionmentioning
confidence: 99%